"You can only claim your yard and not a country": exploring context, discourse and practices of cosmopolitanism amongst African migrants in Johannesburg - Haupt, Iriann (My University, 2010)
Adopting a social constructionist methodology, this research explores the contexts, discourse and practices of cosmopolitanism amongst African migrants in Johannesburg, South(ern) Africa’s economic hub and top migrant destination. The research argues that the central function of this cosmopolitanism is to serve as a counter-narrative to an exclusive South African nationalism and as an expression of a more general struggle to overcome the unwarranted limitations of being born in a country which does not provide enough opportunities. On the basis of both qualitative and quantitative data collected between 2006 and 2008 in Johannesburg, this study challenges the still widely held assumption that cosmopolitanism is not for those whose mobility is ‘unprivileged’ and argues that this assumption becomes particularly unsustainable once situated in the contexts of Africa’s unachieved nation-states, hyper-diverse urban centres and multiple alternative systems of belonging and identity. Instead, this study argues that it is exactly these conditions that have actually allowed a particular type of cosmopolitanism to emerge rather than having suppressed it. The three empirical chapters explore how migrants’ counter-narrative to discourses of nationalism, exclusion and pathologisation of migration constructs notions of mobility and space in particularly cosmopolitan, de-territorialised terms; generates a concept of cultural diversity and the engagement with the Other as normal, enriching and unproblematic; and establishes a more inclusive and multifaceted cosmopolitan social order that is claimed to be morally superior to that of nationalism. Finally, the conclusion provides some pointers towards three central imperatives for future research on cosmopolitanism: firstly, the imperative to address the present disconnect between cosmopolitanism from above and from below – and as part of that the lack of attention to empirical forms of cosmopolitanism; secondly, the importance of paying more attention to the social, cultural and economic contexts in which forms of empirical cosmopolitanism are embedded; and, thirdly, the need to overcome the three ‘isms’ that the majority of research on cosmopolitanism and migration remains stunted by: ethnocentrism, class-centrism and, somewhat ironically, methodological nationalism. The study argues that if we want to know more about how individuals become cosmopolitan agents of change and reformulate social orders ‘from below’, we should begin to treat migrant populations, and particularly those who move within and across the African continent, as a crucial source of knowledge about how to negotiate both the uncertainties and the opportunities that are intrinsic to more de-territorialised, post-national forms of social organisation and identity.
Keywords: South Africa; Johannesburg; migration; cosmopolitanism; discourse analysis